Mesenchymal tumor organoid models recapitulate rhabdomyosarcoma subtypes - Michael T Meister; Marian J A Groot Koerkamp; Terezinha de Souza; Willemijn B Breunis; Ewa Frazer‐Mendelewska; Mariël Brok; Jeff DeMartino; Freek Manders; Camilla Calandrini; Hinri H D Kerstens; Alex Janse; M Emmy M Dolman; et al. (EMBO Molecular Medicine, 2022)
Abstract Rhabdomyosarcomas (RMS) are mesenchyme‐derived tumors and the most common childhood soft tissue sarcomas. Treatment is intense, with a nevertheless poor prognosis for high‐risk patients. Discovery of new therapies would benefit from additional preclinical models. Here, we describe the generation of a collection of 19 pediatric RMS tumor organoid (tumoroid) models (success rate of 41%) comprising all major subtypes. For aggressive tumors, tumoroid models can often be established within 4–8 weeks, indicating the feasibility of personalized drug screening. Molecular, genetic, and histological characterization show that the models closely resemble the original tumors, with genetic stability over extended culture periods of up to 6 months. Importantly, drug screening reflects established sensitivities and the models can be modified by CRISPR/Cas9 with TP53 knockout in an embryonal RMS model resulting in replicative stress drug sensitivity. Tumors of mesenchymal origin can therefore be used to generate organoid models, relevant for a variety of preclinical and clinical research questions.